Preparation method of lithium metal-electrolyte composite structure and lithium battery
By coating the composite electrolyte dispersion on the lithium metal sheet and drying and rolling the process, a lithium metal-electrolyte composite structure with toughness and high conductivity is formed, and the energy consumption of the existing thin film-type lithium metal negative electrode production process is solved. The poor contact with the interface has achieved a more uniform and efficient preparation of lithium metal electrodes.
Patent Information
- Application Number
- CN202411348771.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The existing production process of thin-film lithium metal negative electrodes has problems such as high energy consumption, alloy segregation, poor interface contact and difficult process parameter control, making it difficult to achieve mass production.
The composite electrolyte dispersion is used to coat the surface of the lithium metal sheet, containing polymer and oxide electrolyte, and the lithium metal-electrolyte composite structure is formed after drying and rolling, improving the toughness and flexibility of the electrolyte material and reducing the processing process of lithium metal. stress concentration in.
The formed lithium metal-electrolyte composite structure has a smaller surface friction, which reduces local wrinkles and stickiness, improves the uniformity and conductivity of lithium metal sheets, and is suitable for mass production.
Smart Images

Figure CN119230959A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy, and in particular to lithium batteries. Background Art
[0002] Solid-state batteries with high energy density and safety are ideal candidates for the next generation of energy storage applications. They are expected to break through the technical bottleneck of liquid lithium-ion batteries and achieve higher energy density, longer cycle life and better safety performance. In addition, solid-state batteries can introduce lithium metal anodes with higher specific capacity. The theoretical specific capacity of lithium metal anodes is 3680mAh / g, which is much higher than the theoretical specific capacity of carbon-based graphite materials of only 372mAh / g, which is conducive to improving the energy density of lithium batteries. Because lithium metal is more active and softer, it is difficult to mechanically process it into a thin and regular lithium foil like an electrode sheet. At present, the production process technology routes of thin-film lithium metal anodes mainly include hot melt method, composite metal method and electrodeposition method. However, the hot melt method consumes more energy, the composite metal method is prone to alloy segregation and has the problem of poor interface contact, and the electrodeposition method requires high precision control of process parameters, and is often time-consuming and difficult to mass produce. At present, the production process of thin-film lithium metal anodes still needs to be improved. Summary of the invention
[0003] The embodiments of the present application provide a method for preparing a lithium metal-electrolyte composite structure and a lithium battery to solve the technical problem that the production process of thin-film lithium metal negative electrodes still needs to be improved.
[0004] In a first aspect, an embodiment of the present application provides a method for preparing a lithium metal-electrolyte composite structure, the method for preparing the lithium metal-electrolyte composite structure comprising the following steps:
[0005] Providing a composite electrolyte dispersion, wherein a polymer and an oxide electrolyte are dispersed in the composite electrolyte solution;
[0006] Applying the composite electrolyte dispersion onto the surface of the lithium metal sheet to form a liquid film;
[0007] Drying the liquid film to obtain a prefabricated composite structure;
[0008] The prefabricated composite structure is subjected to a rolling process to obtain a lithium metal-electrolyte composite structure.
[0009] In some embodiments of the present application, the polymer is at least one of polyvinylidene fluoride, polymethyl methacrylate, poly(vinylidene fluoride-co-hexafluoropropylene), polyimide, and aramid.
[0010] In some embodiments of the present application, the oxide electrolyte is at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and lithium lanthanum zirconium titanium oxide.
[0011] In some embodiments of the present application, the particle size of the oxide electrolyte is 0.4-2 μm.
[0012] In some embodiments of the present application, in the composite electrolyte dispersion, the weight percentage concentration of the polymer is 1% to 10%; and / or,
[0013] In the composite electrolyte dispersion, the weight percentage concentration of the oxide electrolyte is 20% to 40%.
[0014] In some embodiments of the present application, the thickness of the liquid film is 2-5 μm.
[0015] In some embodiments of the present application, the roller pressing pressure is 1 MPa to 6 MPa, the speed is 0.1 m / s to 3 m / s, the time is 0.1 h to 5 h, and the temperature is 25 to 100°C.
[0016] In some embodiments of the present application, the thickness of the lithium metal sheet is 50-60 μm.
[0017] In some embodiments of the present application, the thickness of the lithium metal-electrolyte composite structure is 20 to 30 μm.
[0018] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises a lithium metal-electrolyte composite structure prepared by the method described in any embodiment of the first aspect.
[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0020] The preparation method of the lithium metal-electrolyte composite structure provided in the embodiment of the present application, the composite electrolyte dispersion contains a polymer and an oxide electrolyte, and the composite electrolyte dispersion is applied to the surface of the lithium metal sheet to form a tough and relatively soft electrolyte material after drying, which can easily disperse the stress of the lithium metal sheet during the rolling process; and the surface friction between the electrolyte material and the lithium metal is small, and the lithium is not prone to local wrinkling and sticking. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0023] Figure 1 A schematic diagram of a process for preparing a lithium metal-electrolyte composite structure provided in an embodiment of the present application. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0025] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0027] The existing production process of thin-film lithium metal negative electrodes still needs to be improved.
[0028] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:
[0029] In a first aspect, an embodiment of the present application provides a method for preparing a lithium metal-electrolyte composite structure, the method for preparing the lithium metal-electrolyte composite structure comprising the following steps:
[0030] S1: providing a composite electrolyte dispersion, wherein a polymer and an oxide electrolyte are dispersed in the composite electrolyte solution;
[0031] S2: applying the composite electrolyte dispersion onto the surface of the lithium metal sheet to form a liquid film;
[0032] S3: drying the liquid film to obtain a prefabricated composite structure;
[0033] S4: rolling the prefabricated composite structure to obtain a lithium metal-electrolyte composite structure.
[0034] It is easy to understand that lithium is a relatively soft metal with low deformation resistance, strong ductility, and active properties. It is prone to stress concentration during processing, which leads to irregular shape, local wrinkles and sticking.
[0035] The composite electrolyte dispersion described in the present application contains a polymer and an oxide electrolyte. When the composite electrolyte dispersion is applied to the surface of a lithium metal sheet, a tough and relatively soft electrolyte material is formed after drying, which can easily disperse the stress of the lithium metal sheet during the rolling process. In addition, the surface friction between the electrolyte material and the lithium metal is relatively small, and lithium is not prone to local wrinkling and sticking.
[0036] In addition, the electrolyte material and lithium metal can be brought into closer contact during the rolling process.
[0037] In some embodiments of the present application, the polymer is at least one of polyvinylidene fluoride, polymethyl methacrylate, poly(vinylidene fluoride-co-hexafluoropropylene), polyimide, and aramid.
[0038] It is easy to understand that the above polymers all have good toughness and film-forming properties and are easily available on the market, and are highly applicable in this application.
[0039] In some embodiments of the present application, the oxide electrolyte is at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and lithium lanthanum zirconium titanium oxide.
[0040] It is easy to understand that lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and lithium lanthanum zirconium titanium oxide all have good gel-forming properties, high electrical conductivity and strong stability, and are easily available on the market, and are highly applicable in this application.
[0041] In some embodiments of the present application, the particle size of the oxide electrolyte is 0.4-2 μm.
[0042] The beneficial effect of the oxide electrolyte having a particle size of 0.4 to 2 μm is that it can ensure that the oxide electrolyte and the polymer can be evenly mixed, and can also ensure that the electrolyte material formed by the liquid film after drying has high ionic conductivity. At the same time, the difficulty of preparing the oxide electrolyte is not too high due to the small particles.
[0043] As an example, the particle size of the oxide electrolyte may be 0.4 μm, 0.8 μm, 1.2 μm, 1.6 μm, or 2 μm.
[0044] In some embodiments of the present application, in the composite electrolyte dispersion, the weight percentage concentration of the polymer is 1% to 10%; and / or,
[0045] In the composite electrolyte dispersion, the weight percentage concentration of the oxide electrolyte is 20% to 40%.
[0046] It is easy to understand that the beneficial effect of the weight percentage concentration of the polymer being 1% to 10% is that the polymer can be dispersed relatively evenly in the composite electrolyte dispersion and the electrolyte material formed by the liquid film after drying can be ensured to have good moldability and toughness.
[0047] It is easy to understand that the beneficial effect of the weight percentage concentration of the oxide electrolyte being 20% to 40% is that the oxide electrolyte can be relatively uniformly distributed in the composite electrolyte dispersion and the electrolyte material formed by the liquid film after drying can be ensured to have a higher conductivity.
[0048] In some embodiments of the present application, the thickness of the liquid film is 2-5 μm.
[0049] The beneficial effect of the liquid film having a thickness of 2 to 5 μm is that when the prefabricated composite structure is subjected to a rolling process, it can provide sufficient buffering for the rolled lithium metal sheets and enable the lithium metal sheets to be fully rolled.
[0050] As an example, the thickness of the liquid film may be 2 μm, 3 μm, 4 μm, or 5 μm.
[0051] In some embodiments of the present application, the roller pressing pressure is 1 MPa to 6 MPa, the speed is 0.1 m / s to 3 m / s, the time is 0.1 h to 5 h, and the temperature is 25 to 100°C.
[0052] In some embodiments of the present application, the thickness of the lithium metal sheet is 50-60 μm.
[0053] In some embodiments of the present application, the thickness of the lithium metal-electrolyte composite structure is 20 to 30 μm.
[0054] The beneficial effect of the thickness of the lithium metal-electrolyte composite structure being 20 to 30 μm is that the lithium metal-electrolyte composite structure has sufficient flexibility and the thickness of the lithium metal in the lithium metal-electrolyte composite structure is easily maintained at a uniform thickness.
[0055] As examples, the thickness of the lithium metal-electrolyte composite structure is 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, or 30 μm.
[0056] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises a lithium metal-electrolyte composite structure prepared by the method described in any embodiment of the first aspect.
[0057] It is easy to understand that the lithium metal-electrolyte composite structure can serve as a negative electrode and electrolyte structure in a lithium battery.
[0058] The lithium battery is realized based on a lithium metal-electrolyte composite structure prepared by the method described in any embodiment of the first aspect. The specific implementation of the lithium battery can refer to the above embodiments and common knowledge in the art. Since the lithium battery adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0059] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0060] Example 1
[0061] This embodiment provides a method for preparing a lithium metal-electrolyte composite structure, and the method for preparing the lithium metal-electrolyte composite structure comprises the following steps:
[0062] Sa: composite electrolyte dispersion was prepared with N-methylpyrrolidone as solvent and polymer and oxide electrolyte as solute;
[0063] Sb: coating the composite electrolyte dispersion on both sides of the lithium metal sheet to form a 3 μm thick liquid film;
[0064] Sc: drying the liquid film to obtain a prefabricated composite structure;
[0065] Sd: The prefabricated composite structure is subjected to a roll-pressing process to obtain a lithium metal-electrolyte composite structure.
[0066] The polymer is poly(vinylidene fluoride-co-hexafluoropropylene).
[0067] The oxide electrolyte is lithium aluminum titanium phosphate.
[0068] The particle size of the oxide electrolyte is 1 μm.
[0069] In the composite electrolyte dispersion, the weight percentage concentration of the polymer is 2%.
[0070] In the composite electrolyte dispersion, the weight percentage concentration of the oxide electrolyte is 10%.
[0071] The roller pressing was performed at a pressure of 1.5 MPa, a speed of 0.5 m / s, a time of 0.1 h and a temperature of 50°C.
[0072] The thickness of the lithium metal sheet is 50 μm.
[0073] The thickness of the lithium metal-electrolyte composite structure is 25 μm.
[0074] Example 2
[0075] This embodiment provides a method for preparing a lithium metal-electrolyte composite structure, and the method for preparing the lithium metal-electrolyte composite structure comprises the following steps:
[0076] Sa: composite electrolyte dispersion was prepared with N-methylpyrrolidone as solvent and polymer and oxide electrolyte as solute;
[0077] Sb: coating the composite electrolyte dispersion on both sides of the lithium metal sheet to form a 3 μm thick liquid film;
[0078] Sc: drying the liquid film to obtain a prefabricated composite structure;
[0079] Sd: The prefabricated composite structure is subjected to a roll-pressing process to obtain a lithium metal-electrolyte composite structure.
[0080] The polymer is poly(vinylidene fluoride-co-hexafluoropropylene).
[0081] The oxide electrolyte is lithium aluminum titanium phosphate.
[0082] The particle size of the oxide electrolyte is 1 μm.
[0083] In the composite electrolyte dispersion, the weight percentage concentration of the polymer is 2%.
[0084] In the composite electrolyte dispersion, the weight percentage concentration of the oxide electrolyte is 20%.
[0085] The roller pressing was performed at a pressure of 1.5 MPa, a speed of 0.5 m / s, a time of 0.1 h and a temperature of 50°C.
[0086] The thickness of the lithium metal sheet is 50 μm.
[0087] The thickness of the lithium metal-electrolyte composite structure is 26 μm.
[0088] Example 3
[0089] This embodiment provides a method for preparing a lithium metal-electrolyte composite structure, and the method for preparing the lithium metal-electrolyte composite structure comprises the following steps:
[0090] Sa: composite electrolyte dispersion was prepared with N-methylpyrrolidone as solvent and polymer and oxide electrolyte as solute;
[0091] Sb: coating the composite electrolyte dispersion on both sides of the lithium metal sheet to form a 3 μm thick liquid film;
[0092] Sc: drying the liquid film to obtain a prefabricated composite structure;
[0093] Sd: The prefabricated composite structure is subjected to a roll-pressing process to obtain a lithium metal-electrolyte composite structure.
[0094] The polymer is poly(vinylidene fluoride-co-hexafluoropropylene).
[0095] The oxide electrolyte is lithium aluminum titanium phosphate.
[0096] The particle size of the oxide electrolyte is 1 μm.
[0097] In the composite electrolyte dispersion, the weight percentage concentration of the polymer is 2%.
[0098] In the composite electrolyte dispersion, the weight percentage concentration of the oxide electrolyte is 30%.
[0099] The roller pressing was performed at a pressure of 1.5 MPa, a speed of 0.5 m / s, a time of 0.1 h and a temperature of 50°C.
[0100] The thickness of the lithium metal sheet is 50 μm.
[0101] The thickness of the lithium metal-electrolyte composite structure is 27 μm.
[0102] Example 4
[0103] This embodiment provides a method for preparing a lithium metal-electrolyte composite structure, and the method for preparing the lithium metal-electrolyte composite structure comprises the following steps:
[0104] Sa: composite electrolyte dispersion was prepared with N-methylpyrrolidone as solvent and polymer and oxide electrolyte as solute;
[0105] Sb: coating the composite electrolyte dispersion on both sides of the lithium metal sheet to form a 3 μm thick liquid film;
[0106] Sc: drying the liquid film to obtain a prefabricated composite structure;
[0107] Sd: The prefabricated composite structure is subjected to a roll-pressing process to obtain a lithium metal-electrolyte composite structure.
[0108] The polymer is poly(vinylidene fluoride-co-hexafluoropropylene).
[0109] The oxide electrolyte is lithium aluminum titanium phosphate.
[0110] The particle size of the oxide electrolyte is 1 μm.
[0111] In the composite electrolyte dispersion, the weight percentage concentration of the polymer is 2%.
[0112] In the composite electrolyte dispersion, the weight percentage concentration of the oxide electrolyte is 20% to 40%.
[0113] The roller pressing was performed at a pressure of 1.5 MPa, a speed of 0.5 m / s, a time of 0.1 h and a temperature of 50°C.
[0114] The thickness of the lithium metal sheet is 50 μm.
[0115] The thickness of the lithium metal-electrolyte composite structure is 29 μm.
[0116] Example 5
[0117] The only difference between this embodiment and embodiment 1 is that in step Sb, the composite electrolyte dispersion is only coated on one surface of the lithium metal sheet.
[0118] The details are as follows:
[0119] This embodiment provides a method for preparing a lithium metal-electrolyte composite structure, and the method for preparing the lithium metal-electrolyte composite structure comprises the following steps:
[0120] Sa: composite electrolyte dispersion was prepared with N-methylpyrrolidone as solvent and polymer and oxide electrolyte as solute;
[0121] Sb: coating the composite electrolyte dispersion onto one surface of the lithium metal sheet to form a 3 μm thick liquid film;
[0122] Sc: drying the liquid film to obtain a prefabricated composite structure;
[0123] Sd: The prefabricated composite structure is subjected to a roll-pressing process to obtain a lithium metal-electrolyte composite structure.
[0124] The polymer is poly(vinylidene fluoride-co-hexafluoropropylene).
[0125] The oxide electrolyte is lithium aluminum titanium phosphate.
[0126] The particle size of the oxide electrolyte is 1 μm.
[0127] In the composite electrolyte dispersion, the weight percentage concentration of the polymer is 2%.
[0128] In the composite electrolyte dispersion, the weight percentage concentration of the oxide electrolyte is 10%.
[0129] The roller pressing was performed at a pressure of 1.5 MPa, a speed of 0.5 m / s, a time of 0.1 h and a temperature of 50°C.
[0130] The thickness of the lithium metal sheet is 50 μm.
[0131] The thickness of the lithium metal-electrolyte composite structure is 23 μm.
[0132] Related experiments and effect data:
[0133] The lithium metal-electrolyte composite structure obtained in Examples 1 to 5 was tested as a negative electrode of a lithium battery. The specific test method is as follows:
[0134] The thickness of the lithium metal-electrolyte composite structure was measured using a micrometer;
[0135] The lithium metal-electrolyte composite structure and stainless steel sheet were assembled into a symmetrical cell, and the ionic conductivity was measured by AC impedance spectroscopy.
[0136] The lithium metal-electrolyte composite structure and commercial lithium sheets are combined into a symmetrical battery at a current density of 1 mA / cm 2 , the cycle capacity is 1 mAh / cm 2 , after 50 cycles, the stable polarization voltage was recorded.
[0137] The ionic conductivity and polarization voltage obtained from the test are shown in Table 1.
[0138] Table 1 Ionic conductivity and polarization voltage test results of Examples 1 to 5
[0139] Thickness(μm) Ionic conductivity (mS / cm) Polarization voltage(mV) Example 1 25 0.8 38mV Example 2 26 1.2 33mV Example 3 27 1.4 29mV Example 4 29 1.8 25mV Example 5 23 0.5 35mV
[0140] Examples 1 to 4 strictly control variables, and only the content of the oxide electrolyte is different. As can be seen from Table 1, as the content of the oxide electrolyte increases, the thickness and ionic conductivity of the lithium metal-electrolyte composite structure increase, and the polarization voltage decreases, which shows that under the conditions of Examples 1 to 4, increasing the content of the oxide electrolyte is beneficial to increasing the ionic conductivity of the lithium metal-electrolyte composite structure and the diffusion capacity of ions on the surface of lithium metal to the electrolyte. The only difference between Example 5 and Example 1 is that Example 5 only coats a single layer of liquid film, and the ionic conductivity and polarization voltage are both reduced compared to Example 1. Overall, the technical solution of only coating a single layer of liquid film is compared with the technical solution of coating on both sides, and the ionic conductivity of the lithium metal-electrolyte composite structure obtained is reduced.
[0141] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0142] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single (individual) or plural (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, and c can be single or multiple, respectively.
[0143] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a lithium metal-electrolyte composite structure, characterized in that: The preparation method of the lithium metal-electrolyte composite structure comprises the following steps: Providing a composite electrolyte dispersion, wherein a polymer and an oxide electrolyte are dispersed in the composite electrolyte solution; Applying the composite electrolyte dispersion onto the surface of the lithium metal sheet to form a liquid film; Drying the liquid film to obtain a prefabricated composite structure; The prefabricated composite structure is subjected to a rolling process to obtain a lithium metal-electrolyte composite structure.
2. The method for preparing a lithium metal-electrolyte composite structure according to claim 1, characterized in that: The polymer is at least one of polyvinylidene fluoride, polymethyl methacrylate, poly(vinylidene fluoride-co-hexafluoropropylene), polyimide, and aramid.
3. The method for preparing a lithium metal-electrolyte composite structure according to claim 1, characterized in that: The oxide electrolyte is at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and lithium lanthanum zirconium titanium oxide.
4. The method for preparing a lithium metal-electrolyte composite structure according to claim 1, characterized in that: The particle size of the oxide electrolyte is 0.4-2 μm.
5. The method for preparing a lithium metal-electrolyte composite structure according to claim 1, characterized in that: In the composite electrolyte dispersion, the weight percentage concentration of the polymer is 1% to 10%; and / or, In the composite electrolyte dispersion, the weight percentage concentration of the oxide electrolyte is 20% to 40%.
6. The method for preparing a lithium metal-electrolyte composite structure according to claim 1, characterized in that: The thickness of the liquid film is 2-5 μm.
7. The method for preparing a lithium metal-electrolyte composite structure according to claim 1, characterized in that: The roller pressing has a pressure of 1 MPa to 6 MPa, a speed of 0.1 m / s to 3 m / s, a time of 0.1 h to 5 h, and a temperature of 25 to 100° C.
8. The method for preparing a lithium metal-electrolyte composite structure according to claim 1, characterized in that: The thickness of the lithium metal sheet is 50-60 μm.
9. The method for preparing a lithium metal-electrolyte composite structure according to claim 1, characterized in that: The thickness of the lithium metal-electrolyte composite structure is 20 to 30 μm.
10. A lithium battery, characterized in that: The lithium battery comprises a lithium metal-electrolyte composite structure prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method for solid-state lithium-ion battery
CN108110324A
Polymer composite film and preparation method thereof, composite electrode plate and preparation method thereof, and lithium metal secondary battery
CN111499995A
Pre-lithiated negative plate and preparation method and application thereof
CN112072074A
Preparation method of lithium metal negative electrode and lithium metal negative electrode
CN113299886A
Positive pole piece of lithium ion battery, preparation method of positive pole piece and lithium battery
CN116779779A
Cited By
Method for preparing lithium metal-electrolyte composite structure, and lithium battery
WO2026067294A1
